ANALISIS PENGARUH INSENTIF TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI (Studi Pada Karyawan Perusahaan Air Minum Kabupaten Jepara) - Mera Diviani, Gracetiara; Djastuti, Indi (Diponegoro Journal of Management, 2015)
Incentives as a means of motivation that encourages employees to work with optimal performance, which is intended as an extra income outside of salaries or wages that have been determined. This study entitled "Analysis of incentives influence on job satisfaction and employee performance". Incentives can explain the employee's performance significantly by using job satisfaction as a mediating variable. The purpose of this study was to determine and analyze whether incentives can affect employee performance and job satisfaction of employees at the office taps Kabupanten Jepara. The population of this research are 100 people and this researchÂ  use of unrestricted random sampling technique or the total sampling, ie a total of 100 people as a whole is taken as the sample population. Reality on the ground finally set only 93 respondents, resulting in a decrease of 7%, and the implications of the decline in the percentage of the sample size is still considered to meet the principle representitas research, because below 30 percent.This study used multiple linear regression analysis. This studi test how incentives and job satisfaction variable take effect on the dependent variable it is employee performance.The results showed that there is a positive and significant effect of incentives on employee performance can be explained by the model, which is 70.7%, there is a positive and significant direct effect on job satisfaction and employee performance can be explained in our model by 63.1%, and incentives sigifikan positive effect on job satisfaction and employee can be explained by the model at 49.7%.